2013
DOI: 10.1038/bjc.2012.547
|View full text |Cite
|
Sign up to set email alerts
|

A central review of histopathology reports after breast cancer neoadjuvant chemotherapy in the neo-tango trial

Abstract: Background:Neo-tAnGo, a National Cancer Research Network (NCRN) multicentre randomised neoadjuvant chemotherapy trial in early breast cancer, enroled 831 patients in the United Kingdom. We report a central review of post-chemotherapy histopathology reports on the surgical specimens, to assess the presence and degree of response.Methods:A central independent two-reader review (EP and HME) of histopathology reports from post-treatment surgical specimens was performed. The quality and completeness of pathology re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…11 It is possible that should such standardisation be adopted, a measure of response such as RCB could be calculated locally. Also, although there is some evidence that pathologists are better at assessing chemotherapy response by reading pathology reports than are practicing clinicians 12 this was not borne out by our data. It was evident on review of some of the cases where there were discrepancies between report-review and central review that this was due to missing slides.…”
contrasting
confidence: 46%
“…11 It is possible that should such standardisation be adopted, a measure of response such as RCB could be calculated locally. Also, although there is some evidence that pathologists are better at assessing chemotherapy response by reading pathology reports than are practicing clinicians 12 this was not borne out by our data. It was evident on review of some of the cases where there were discrepancies between report-review and central review that this was due to missing slides.…”
contrasting
confidence: 46%
“…The last few years NAST is offered more and more often to patients with early breast cancer and it has almost become routine for patients to receive systemic therapy [11,28]. However as a result of NAST, the correlation of clinicopathological and radiological response with residual tumour could not be defined accurately [29], although with the introduction of magnetic resonance the accuracy in discriminating residual disease versus pCR has improved [30].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, pathologists in their daily routine practice have to deal with specimens where important parameters for reporting are missing. The neo-tAnGo trial revealed large variations in handling and reporting of post-NAST breast cancer specimens [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoadjuvant treatment (NAT) has represented a major paradigm shift in the management of breast cancer over the last years and it is increasingly being used (1,2). In the context of clinical trials NAT has offered a unique opportunity for the evaluation of treatment response, with pathological complete response (pCR) acting as a surrogate marker of survival, thus 1) allowing more rapid assessment of the efficacy of new chemotherapeutic agents, 2) enabling early ending of ineffective treatments, and 3) providing an opportunity to individualize patient treatment at early stages (1).…”
Section: Background and Critical Issuesmentioning
confidence: 99%